Non-Gaussian elliptic-flow fluctuations in PbPb collisions at √sNN = 5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
Event-by-event fluctuations in the elliptic-flow coefficient v2 are studied in PbPb collisions at √sNN = 5.02 TeV using the CMS detector at the CERN LHC. Elliptic-flow probability distributions p(v2) for charged particles with transverse momentum 0.3 < pT < 3.0 GeV/c and pseudorapidity |η| < 1.0 are determined for different collision centrality classes. The moments of the p(v2) distributions are used to calculate the v2 coefficients based on cumulant orders 2, 4, 6, and 8. A rank ordering of the higher-order cumulant results and nonzero standardized skewness values obtained for the p(v2) distributions indicate nonGaussian initial-state fluctuations. Bessel–Gaussian and elliptic power fits to the flow distributions are studied to characterize the initial-state spatial anisotropy.